An Examination of Al-Ghazali's Philosophical Thought: Building the Path to Spiritual Perfection - Sofwatun Nida; Arif Zefrizen (Islamic Religious Education Master Program Universitas Islam Internasional Darullughah Wadda'wah, 2026)
This research aims to examine the philosophical thoughts of Imam Al-Ghazali and relate them in the modern era to build a path to human spiritual perfection. This research is a qualitative type with a library research approach, accompanied by primary sources in the form of books and secondary sources of several journal articles. Research data were collected through various books and journals as sources of information and then analyzed using content analysis techniques. The result of this research is to achieve spiritual perfection through the integration of ethics, Sufism, philosophy, and epistemology. Al-Ghazali emphasized the importance of ethics as a basis, where humans are expected to imitate divine traits, such as compassion and wisdom, to approach self-perfection. Through naturalizing the view that God is the active creator who governs the universe, Al-Ghazali invites humans to adopt a position of humility and resignation, realizing that everything comes from God’s will. Overall, Al-Ghazali combines the elements of reason, ethics, and intuition in a harmonious path towards God, providing humans with a way to achieve deep spiritual balance as well as awareness of divine reality in everyday life.